Kajian Budaya dalam Konteks Dakwah Serantau - Jaffary Awang (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2002)
Important to the rrusston of dakwab Islam is the understanding of the local culture within which the dakwab process is going on. A thorough understanding of such a local culture opens the ways to dissemination of Islam. A question remains to what extent the da'is take advantage of the cultural researches' findings for the sake of proselytization. Indeed the cultural features are especially crucial to the development o f dakwah throughout Malaysia and Indonesia This means that serious studies on the social structures have to be an integrated part of dakwah studies.This study will raise some cultural isues having something to do with and can be exploited by the da 'is in Malaysia and Indonesia. It focuses on the value systems, etnic relations, and the world views of each society. I argue that these three aspects of culture have the necesary potentials to mobilize dakwah activities.